Incidence of social media marketing strategies in restaurant customer loyalty in Guayaquil - Poveda-Anchundia, Tatiana (2023)
This research explores the incidence of social networks in customer loyalty initiatives of a group of gastronomic ventures in the initial phase, also known as "entrepreneurship", in the city of Guayaquil. Through a quantitative study that focuses on the content analysis and engagement of Instagram social network accounts, and social media marketing strategies deployed through these platforms, it is argued that there is a disconnect between the way in which the owners of restaurants used technology for customer loyalty. In the year 2021, which corresponds to the period of this study, it was evidenced that restaurant owners and staff used social networks without knowing how they could help them establish lasting relationships with their existing customers. Hence, on Instagram, the accounts of these restaurants reflected high levels of engagement without demonstrating high levels of customer loyalty. So, this research concludes that the number of Instagram posts will not necessarily be reflected in higher levels of engagement and, in an increase in customer loyalty, proposing initiatives for loyalty in these ventures.